P254 Once-daily Tiotropium And Olodaterol Fixed-dose Combination Via The Respimat® Improves Outcomes Versus Mono-components In Copd In Two 1-year Studies. (10th November 2014) - Buhl, R; Derom, E; Ferguson, G; Pizzichini, E; Reid, J; Watz, H; Grönke, L; Hamilton, A; Tetzlaff, K; Korducki, L; Huisman, H; Waitere-Wijker, S; et al.
Abstract : Introduction: Tiotropium (T), a once-daily long-acting muscarinic antagonist, is a well-established first-line maintenance treatment in chronic obstructive pulmonary disease (COPD); olodaterol (O) is a once-daily long-acting β2 -agonist that has recently gained approval in several countries. Two Phase III replicate pivotal studies assessed the efficacy and safety of fixed-dose combinations of T and O (T+O) delivered via Respimat ® Soft Mist™ inhaler in patients with GOLD 2–4 COPD. Methods: Two 52-week, double-blind, parallel-group studies randomised 5162 patients to O 5 µg, T 2.5 µg, T 5 µg, T+O 2.5/5 µg or T+O 5/5 µg. Primary efficacy end points were trough forced expiratory volume in 1 second (FEV1 ) response (ie change from baseline), FEV1 area under the curve from 0–3 h and St George's Respiratory Questionnaire (SGRQ) total score after 24 weeks. Pooled data from the two studies are presented here; lung function from the individual studies will subsequently be provided. Results: All treatments resulted in clinically relevant improvements in lung function, with significant increases with both T+O doses over the individual components (p1 responses were 0.055 L (O 5 µg), 0.073 L (T 2.5 µg), 0.080 L (T 5 µg), 0.118 L (T+O 2.5/5 µg) and 0.140 L (T+O 5/5 µg). SGRQ total scores improved by 5.1 (O 5 µg), 5.7 (T 2.5 µg), 5.6 (T 5 µg), 6.2 (T+O 2.5/5 µg) and 6.8 points (T+O 5/5 µg); differences between T+O 5/5 µg and O 5 µg and T 5 µg were statistically significant (p Conclusions: T+O 5/5 µg significantly improved lung function and provided symptomatic benefit over O 5 µg and T 5 µg.